The Use of Chemical Control Within Coercive Controlling Intimate Partner Violence and Abuse - Walker, Sarah-Jane (Violence against women, 2023)
This paper explores the use of chemical control by perpetrators as part of coercive controlling intimate partner violence and abuse, defined as the nonconsenting use of prescribed and nonprescribed medication (including vaccines), and/or other substances to coerce or control, reducing the victim-survivor's capacity for independence, freedom, and health. Based on testimonies of 37 victims-survivors and nine domestic abuse practitioners in the UK we identify varying tactics used to chemically coerce and control, deepening our understanding about the continually changing forms of domestic violence and abuse and enhancing the potential for a more robust response through better informed policy and practice.